Design of micro‐ and macro‐scale polymeric metamaterial solutions for passive and active thermal camouflaging applications. Issue 4 (9th January 2023) - Pisavadia, Harshil; Asad, Asad; Sameoto, Dan; Dolez, Patricia; Hogan, James D.
Abstract: This work utilizes predictive modeling techniques to guide and inform metamaterial design for heat management solutions and thermal radiation control. Specifically, micro‐ and macro‐scale polyethylene‐based solutions are proposed for passive and active thermal camouflage. A micro‐scale post design is proposed for highly‐tunable infrared emissivity based on varying unit cell geometrical configurations. Actively modulating these micro‐features through lateral straining of up to 3% allows for redshifting the emissivity spectrum by up to 0.5 µm. Macro‐scale lenticular lens designs allow for a more passive form of camouflage due to its emissive stability for a range of configurations (e.g., single and sandwiched structures, increasing lens radii and height). Overall, the proposed metamaterial designs allow the tailoring of optical properties to improve thermal radiating performance. Abstract : This manuscript explores the optical performance of micro‐scale posts and macro‐scale lenticular lenses toward development of polyethylene‐based metamaterials for thermal radiation control and signature management. COMSOL Multiphysics software, informed and validated by experiments, is used to reveal: (1) passive camouflage through optical light dispersion capabilities within macro‐lenticular lenses, and (2) redshift of emissivity through strain modulation of the micro‐post design.